Parable church : how the teachings of Jesus shape the culture of our faith - Burnette, Mike, 1980-; Driver, John, 1978- (Grand Rapids Zondervan, 2021)
"In Parable Church, pastor and author Mike Burnette discovers in Jesus's parables a better approach to church life, one focused not on growth strategies or trendy principles, but on a focus towards cultivating the culture of the kingdom revealed through the teachings of Jesus' parables"--
Keywords: Mission of the church; Prodigal son (Parable); Sower (Parable); Talents (Parable)